2016
DOI: 10.1021/acscentsci.6b00169
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties of Polysulfide Species in Lithium–Sulfur Battery Electrolytes: Coupling of Experiment and Theory

Abstract: A comprehensive experimental and theoretical analysis of the isothermal transport of species for the two model ternary-electrolytes with LiTFSI-Li2S4/dioxolane (DOL)-dimethoxyethane (DME) and LiTFSI-Li2S6/DOL-DME formulations is presented. An unambiguous picture of the polysulfide’s mobility is set forth after a detailed investigation of the macroscopic transference number and diffusion coefficients. The new findings of incongruent diffusion for Li2S4 species and high significance of cross-term diffusion coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 44 publications
4
65
0
Order By: Relevance
“…On the other hand, the large number of ionic species in Li-S cells is likely to make the Stefan-Maxwell formulation for concentrated solution unwieldy in modelling Li-S cells, especially since the numerous concentration-dependent transport properties are difficult to obtain experimentally. Nazar et al [37] recently demonstrated the significance of cross-term diffusion coefficients in a ternary polysulfide solution containing S 2− 4 in LiTFSI-DOL/DME. It was discovered via concentration cell and constricted diffusion measurements that S limitation during cell discharge.…”
Section: mentioning
confidence: 99%
“…On the other hand, the large number of ionic species in Li-S cells is likely to make the Stefan-Maxwell formulation for concentrated solution unwieldy in modelling Li-S cells, especially since the numerous concentration-dependent transport properties are difficult to obtain experimentally. Nazar et al [37] recently demonstrated the significance of cross-term diffusion coefficients in a ternary polysulfide solution containing S 2− 4 in LiTFSI-DOL/DME. It was discovered via concentration cell and constricted diffusion measurements that S limitation during cell discharge.…”
Section: mentioning
confidence: 99%
“…However, the severe shuttle effect and dendrite growth, and the inferior Coulombic efficiency that characterize these Li‐S batteries have greatly limited their lifespan 4, 8, 9, 10. Although much effort has been expended in the development of novel sulfur‐host electrodes,11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36 separators,37, 38, 39, 40 and electrolytes41, 42, 43, 44, 45 to resolve these issues, some of which are rather dangerous, the results have been at best minimal in improving current Li‐S battery technology. As a result, the cycling life and Coulombic efficiency of Li‐S batteries, especially in the high‐rate regime, are still far behind the state of the art in lithium‐ion battery technology.…”
Section: Introductionmentioning
confidence: 99%
“…The composite also cycled well at 0.2 C rate, delivering an initial capacity of 1180 mAh/g and retaining a capacity of 680mAh/g in the 30th cycle. The electrochemical performance of the composite is an indirect indication of both the availability of the active material for energy conversion and the good physical and chemical confinement of polysulfide species by the polymer and the carbon matrix …”
Section: Resultsmentioning
confidence: 99%
“…The shuttling of the polysulfide species can drastically reduce the efficiency of the charge and discharge processes. In typical constant‐current discharge curves, this can result in high‐ and low‐voltage plateaus …”
Section: Resultsmentioning
confidence: 99%